A fractional splitting algorithm for nonoverlapping domain decomposition for parabolic problem - Daoud, DS; Subasi, D (Wiley-Blackwell, 2002)
In this article we study the convergence of the nonoverlapping domain decomposition for solving large linear system arising from semi-discretization of two-dimensional initial value problem with homogeneous boundary conditions and solved by implicit time stepping using first and two alternatives of second-order FS-methods. The interface values along the artificial boundary condition line are found using explicit forward Euler's method for the first-order FS-method, and for the second-order FS-method to use extrapolation procedure for each spatial variable individually. The solution by the nonoverlapping domain decomposition with FS-method is applicable to problems that requires the solution on nonuniform meshes for each spatial variable, which will enable us to use different time-stepping over different subdomains and with the possibility of extension to three-dimensional problem. (C) 2002 Wiley Periodicals, Inc.
Keywords: fractional splitting; nonoverlapping domains; parabolic equation